Modeling Market Integration and Asymmetric Price Transmission Dynamics of Yam Markets in Ghana - Abunyuwah, Isaac (Journal of Economics and Behavioral Studies, 2020)
Functioning agricultural markets are fundamental to unlock economic growth and to accelerate agricultural development. Understanding the behavior of agriculture markets is crucial for price, poverty and livelihood policy strategies in agrarian economies. To assess price transmission and market efficiencies of Ghanaian yam markets spatial market integration analysis of five major yam markets: Techiman, Tamale, Wa, Kumasi and Accra was conducted. Monthly wholesale price data between January 2006 and June 2018 were used. Results from the momentum threshold autoregressive (M-TAR) model indicated the presence of co-integration and price transmission asymmetries. Thus, price increases in Techiman reference market are more rapidly transmitted to the other regional markets than price reductions. It is recommended that the source of this type of asymmetry be investigated as it favors middlemen at the expense of producers and retailers/consumers for appropriate marketing policy intervention.